PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Dedi Pendra Setiawan; Darlen Sikumbang; Pramudiyanti Pramudiyanti (Universitas Lampung, 2013)
Based on observation with biology teacher in SMP N 1 Merbau Mataram, students learning activities and outcomes were not optimally developed yet. An alternative that can be used to improve learning activities and outcomes is using picture and picture models. This experiment aims to find out the influence of models Picture and Picture towards improvement of students learning activities and outcomes. This study is quasi experiment using pretest posttest group non equivalent design. Sample are students from VIII A and VIII B which obtained by cluster random sampling method. Quantitative data is outcomes that obtained from average of pretest and posttest scores which statistically analyzed with U-test. Qualitative data are student’s learning activities and students responses about applicating model Picture and Picture which descriptively analyzed. Result of this study shown that the average of students outcomes in experimental class are higher than control (experiment= 69,48; control = 45,17). The average of student learning activities percentage in all observed aspects in experimental class shown higher enhancement than control (experiment = 90.8; control = 60.25). The students also gives positive responses to applicating model Picture and Picture.Keywords: human’s growth and development, learning activities and result, picture and picture models.